Effects of Positive Airway Pressure Therapy on Red Blood Cell Proteome from Patients with Obstructive Sleep Apnea - Coelho- Valentim, Cristina (2019)
Introduction: Obstructive Sleep Apnea (OSA) syndrome, a common public health concern, is characterized by recurrent arousals from sleep and intermittent hypoxemia that can lead to metabolic and cardiovascular diseases. We recently demonstrated that OSA syndrome can cause alterations in the red blood cells (RBC) proteome that may be associated with OSA outcomes. Here we intend to investigate whether the positive airway pressure (PAP) treatment can revert/modulate these proteome alterations.